Preventing Urban Crime for Gender Mobility through Human Scale in Trans Semarang Bus Stop - JF Karistie; Anita Ratnasari Rakhmatulloh (TATALOKA, 2020)
Community safety and crime prevention in the context of the livable city have a tight connection with the practice of human scale. Trans Semarang Bus Rapid Transit as a safe transportation mode is becoming the heart of urban activities that connects various social activities. The ideal condition could be achieved when there is an application of the human scale at the bus stop, without external interference in the process of mobility. As grounded evidence, there are 4 crimes cases that reported on Trans Semarang, not including unreported cases. Indicators in this research cover: the time using BRT, the waiting time at the bus stop, and the changing of human behaviour. Hence, a great human scale characteristic will determine the capability of urban transportation society services. Otherwise, bad human scale characteristics might increase the crime rate. The research will focus on identification of the impact on the human scale variables to the crime rate in Trans Semarang bus stop. It will take place in Semarang Central Business District: Pandanaran, Pemuda and Gajahmada as the center of urban activities served by Trans Semarang. It will conduct a quantitative descriptive research method with the cross-tabulation test. The result is human scale indeed has a positive connection with the crime rate.